2020
DOI: 10.35609/jber.2020.5.1(1)
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Culinary Business Performance

Abstract: Objective - Determination of the performance factors of the small culinary business sector is an important aim of this research. The research also aims to analyze the interconnectedness between the factors which generate competitive advantage and improve the performance of small and medium-sized enterprise businesses. Methodology/Technique - Questionnaires were distributed to 115 such enterprises in the culinary field located in the city of Pekanbaru with the use of the cluster area a non-random sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…ratio exceeds 2 when comparing being an employer with employees with the rest of the categories. In feeling completely happy, an employer with employees is 2.16 times more likely to feel this way than anyone in the other professional categories [73].…”
Section: Overall Samplementioning
confidence: 99%
“…ratio exceeds 2 when comparing being an employer with employees with the rest of the categories. In feeling completely happy, an employer with employees is 2.16 times more likely to feel this way than anyone in the other professional categories [73].…”
Section: Overall Samplementioning
confidence: 99%
“…Understanding these differences is critical to tailoring strategies and interventions to the specific needs of each segment. Understanding these differences is critical and aligns to tailor strategies and interventions to the specific needs of each segment [32]- [34]. The research revealed that factors such as business networks, human resource competencies, and marketing innovations play an important role in the performance of small entrepreneurs in the culinary sector [35], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Higher business competitiveness can be achieved through business networks because business actors can specialize so that business is more efficient, reduce transaction costs, and increase flexibility due to trusted partners. Garnasih, et al (2020) in their research show that competitive advantage mediates the effect of business networks on marketing performance.…”
Section: H7 : Competitive Advantage Mediates the Effect Of Business N...mentioning
confidence: 96%